Failure Process Simulation of Interlayered Rocks under Compression - Chi Yao; Sizhi Zeng; Jianhua Yang (Advances in Civil Engineering)
Anisotropy in strength and deformation of rock mass induced by bedding planes and interlayered structures is a vital problem in rock mechanics and rock engineering. The modified rigid block spring method (RBSM), initially proposed for modeling of isotropic rock, is extended to study the failure process of interlayered rocks under compression with different confining pressures. The modified rigid block spring method is used to simulate the initiation and propagation of microcracks. The Mohr–Coulomb criterion is employed to determine shear failure events and the tensile strength criterion for tensile failure events. Rock materials are replaced by an assembly of Voronoi-based polygonal blocks. To explicitly simulate structural planes and for automatic mesh generation, a multistep point insertion procedure is proposed. A typical experiment on interlayered rocks in literature is simulated using the proposed model. Effects of the orientation of bedding planes with regard to the loading direction on the failure mechanism and strength anisotropy are emphasized. Results indicate that the modified RBSM model succeeds in capturing main failure mechanisms and strength anisotropy induced by interlayered structures and different confining pressures.